Predictors of perceived road collision/incident risk among horse users: A survey study from Norway. (October 2020) - Simsekoglu, Özlem; Dalland, Eva B.; Robertsen, Kåre
Highlights: The study aims to examine predictors of perceived traffic risks among horse users. Attitudes strongly predict the perceived road collision/incident risk in traffic. Other road users' actions constitute the biggest source of risk for the horse users. Knowledge about the rules applying to horse use in traffic is relatively low. Abstract: Although horse users in traffic are a vulnerable road user group, traffic safety problems among them are scantly examined by previous research. The main aim of the present study was to examine the role of some demographic variables, traffic safety attitudes, and level of knowledge about rules and regulations applying to horse use in traffic for predicting perceived road collision/incident risk in a sample of horse users in Norway. An online survey was conducted to collect data from a total of 1733 horse users including horse riders and drivers of horse-drawn sulky, wagon or sled. The respondents accessed the survey via a link put to the website of the Norwegian Horse Centre, which is in contact with many different horse user environments in Norway. The majority of the respondents were female and between the ages of 18–30. A multiple regression analysis was conducted to examine the predictors of the perceived collision/incident risk involving other motor vehicles. Results showed that traffic safety attitudes among horse users were the strongest predictor of the perceived collision/incident risk. In particular, horse users reported a negative attitude towards the other road users (e.g. drivers) indicating that they perceive the other road users' actions and approaches as the biggest source of risk in road traffic. The level of knowledge about the rules and regulations applying to horse use, especially in walking and cycling lane, was relatively low among the respondents. However, knowledge about rules and regulations did not appear as a strong predictor of the perceived collision/incident risk. Results indicate the need to increase road users, especially drivers', awareness about the problems and needs of horse users in traffic.